Extensively drug-resistant tuberculosis: first report of a case in Ireland - KEANE, JOSEPH (My University, 2008)
Extensively drug-resistant tuberculosis (XDR-TB) is an emerging global threat. Between 2002 and 2007 sixteen countries in the European Union (EU) reported at least one case of XDR-TB [1]. Infection is characterised by alarming mortality rates in both HIV and non-HIV populations.
Keywords: Drug-resistant tuberculosis (XDR-TB); Global threat